Causes of the European Union"s Decreasing Position in the Global Economy in 2000-2017 - Mucha-Leszko, Bogumiła (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2018)
The subject of the paper is an analysis of the economic results of the main factors affecting GDP growth in the European Union in 2000-2016. The aim is to evaluate the global position of the EU as well as to identify the main factors affecting growth of the EU’s economic potential and effectiveness. The analysis also includes the long-term development gap in the EU-15/EU-28 versus the U.S.A. Quantitative and qualitative criteria were used in the assessment. Quantitative criteria include: growth rates of GDP, investments and exports, the EU’s share in global GDP, and global exports of goods and services. The qualitative criteria are: labour productivity and total factor productivity TFP. The results of the study are as follows: 1) evaluation of the EU position in the global economy (quantitative indicators) show a decline in the EU's share in global GDP, and trade and FDI were not greater than in the U.S.A.; 2) pertaining to the qualitative criteria the United States ranks better; 3) factors contributing the most to the weakening of the global economic position of the EU are: lower investment in the ICT sector compared to the U.S., differentiation of EU members in terms of their ability to grow, socio-economic divergence and a crisis in the eurozone.